Functional Imaging Methods for Assessment of Minimal Residual Disease in Multiple Myeloma: Current Status and Novel ImmunoPET Based Methods - Pandit-Taskar, Neeta (Semin Hematol, 2018)
Imaging plays a key role is assessment of myeloma. Lytic bone lesions are optimally assessed using structural imaging however the structural changes lag in assessment of functional changes in the assessment of disease. Functional imaging with fluoro deoxy glucose positron emission tomography (PET) computerized tomography is useful in assessment of high-risk myeloma, provides prognostic information and is helpful in monitoring therapy response. However, it is nonspecific and may not be optimal in assessing treatment response to immunotherapeutic agents. Specific targeted imaging may allow for better assessment of changes from therapy, that is, based on specific mechanism. ImmunoPET imaging is a novel method to assess targeting of specific antigen by therapeutic antibodies. This review summarizes the role of functional imaging and development of novel immunoPET agents for assessment of treatment response and residual disease.